The Effect of Finger Puppets Media on Students' Listening Skills on the Topic of Indonesian Cultural Wealth in Malaysia - Marpaung, Sri Rejeki; Sari, Mawar (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to determine the effect of finger puppet media on students' listening skills at the Muhammadiyah Kampung Bharu Malaysia Guidance Center on the material of Indonesian cultural wealth. Students have difficulty listening to the learning materials given by the teacher. The approach in this study uses a pre-experimental method with a one-group pretest-posttest design. The population in this study was made up of 15 fourth-grade students who were used as research samples. The instrument used in this study was an observation sheet on students' listening skills. The validity of the research instrument was tested with expert judgment by assessing its feasibility. The data analysis technique used was the t-test with the alternative hypothesis (Ha) accepted and (H0) rejected the hypothesis carried out using statistical package software for social sciences (SPSS). The results of this study indicate that before the treatment was given, the average value was 65.86, and after the treatment was given, the average value was 86.73. The results of the t-test analysis were accepted to produce a significance value of 0.000 with df 15 with a significance level of less than (<0.05), which indicates that H0 is rejected and Ha. Based on the hypothesis test results, it was proven that finger puppet media influenced the listening skills of grade IV students at the Muhammadiyah Guidance Studio, Kampung Bharu, Malaysia.